Use of interferon gamma for treatment of interleukin-10 deficiency - KIRNON STEPHEN; LIU ZHIPING; VILLARETE LORELIE (2008)
A method for treating an IL-10 deficiency in a human subject is described, where a person having an IL-10 deficiency is identified and treated with interferon-tau (IFNtau) at a dose sufficient to increase the IL-10 level.